1991
DOI: 10.1177/088307389100600214
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Leigh's Encephalomyelopathy With Peripheral Neuropathy, Myopathy, and Cardiomyopathy

Abstract: A child with typical histopathologic changes of Leigh's subacute necrotizing encephalomyelopathy presented with a chronic demyelinating neuropathy. During her 11-year course, she developed an unusual myopathy and cardiomyopathy in addition to many of the previously described manifestations of Leigh's disease. Despite an extensive evaluation, the biochemical basis of her condition was never identified. This case demonstrates another unique constellation of clinical alterations associated with subacute necrotizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The neuroradiologic findings did not differ significantly from the findings in patients with dystonia alone. Extrapyramidal rigidity has been a common finding in LS, often combined with dystonia (4,9,19,25,28,31,33,50,60,62,64,65,77); bradykinesia, mask-like facies and cog-wheeling being additional manifestations. Van Erven et al reported 3 cases of LS in whom a hypokinetic-rigid syndrome was the most prominent clinical sign (77).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroradiologic findings did not differ significantly from the findings in patients with dystonia alone. Extrapyramidal rigidity has been a common finding in LS, often combined with dystonia (4,9,19,25,28,31,33,50,60,62,64,65,77); bradykinesia, mask-like facies and cog-wheeling being additional manifestations. Van Erven et al reported 3 cases of LS in whom a hypokinetic-rigid syndrome was the most prominent clinical sign (77).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated involvement of the peripheral nervous system rarely dominates the clinical situation in mitochondrial diseases in infancy and childhood. It is well known that usually asymptomatic chronic peripheral neuropathy can be found in patients with Leigh syndrome [4,9,11,14]. Coker [5] and Stickler et al [20] reported single observations on children with Leigh syndrome and clinically symptomatic acute polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve biopsy during life showed evidence of active demyelination. This case has been previously published (without the videotape) as a case of juvenile Leigh's disease, emphasizing the presence of peripheral neuropathy, myopathy, and cardiomyopathy (19). Unfortunately, mitochondrial enzymes were not assayed, nor was there a search for mitochondrial DNA abnormalities.…”
Section: (Remarks By Paul E Greene)mentioning
confidence: 98%